Hypercalcemia secondary to excessive self-medication with antacids causing acute pancreatitis: a case report - Vassallo, Pietro (Croat Med J, 2019)
Excessive self-medication with over-the-counter drugs is an issue commonly encountered by health care professionals. It can result in uncommon presentations of life-threatening illnesses. These medications are frequently overlooked by clinicians when taking histories from patients, and their risks are often downplayed. We present the case of a 35-year-old woman with acute pancreatitis secondary to hypercalcemia. This condition occurred due to long-term excessive self-administration of calcium-rich antacid tablets. Her clinical course involved multifactorial rebound hypocalcemia after treatment and multiple complications from the abuse of other non-prescription medications. Acute pancreatitis secondary to antacid-induced milk-alkali syndrome has been minimally reported in the literature. There are no reports describing rebound hypocalcemia as a complication of its treatment or presenting this pathology in the context of multiple over-the-counter drug abuse. This case highlights the importance of taking thorough drug histories, including non-prescription medications, in acute clinical assessments.